A self-powered triboelectric nanosensor for detecting the corrosion state of magnesium treated by micro-arc oxidation. Issue 18 (1st April 2019) - Zhai, Yong-Mei; Li, Wei; Chen, Min-Fang; Li, Yan-Kun; Wang, Qi; Wang, Yan-Song
Abstract : Triboelectric nanogenerators prepared by micro-arc-oxidation-treated magnesium were used as a sensor to detect the corrosion state of it in return. Abstract : Magnesium (Mg) is frequently used as a biocompatible implantable material in the human body, but real-time detection of its corrosion state is not well understood. Fortunately, previous studies of triboelectric nanogenerators (TENG) as self-driven sensors in many fields have proposed solutions for this problem. In this work, Mg-based TENG was prepared as a self-driven sensor to detect the corresponding corrosion state of Mg treated by micro-arc oxidation (MAO-Mg). Mg-based sheets and polydimethylsiloxane (PDMS) film were used as triboelectric materials. The output of TENG was optimal under 350 V–800 Hz micro-arc oxidation (MAO) treatment of Mg, and the V oc, I sc and Q sc were 48.5 V, 35.3 μA and 44.2 nC, which were respectively 2.42, 3.42 and 3.27 times that of the untreated devices. Moreover, a linear relationship was found in simulated body fluid (SBF) immersion tests, showing that the rates of decrease in I sc and V oc were respectively 3.48 and 2.74 times the weight reduction rates of MAO-Mg sheets, indicating that our sensors successfully detected the corrosion of MAO-Mg. This work will lay a preliminary foundation for real-time detection of Mg as an implant in the human body (as do other implantable materials), and demonstrates a potential new application for TENG in the biomedical field.